2015
DOI: 10.1007/s12262-015-1220-0
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Easy Technique for the Placement of Seprafilm During Laparoscopic Surgery

Abstract: Laparoscopic surgery is a minimally invasive surgery, and the incidence of postoperative small bowel obstruction (SBO) is not high. However, SBO is a disease that detracts from the benefits of laparoscopic surgery due to the need for additional therapies or prolongation of hospital stay. Seprafilm is effective in reducing adhesions and preventing the occurrence of SBO. However, it is very difficult to place the Seprafilm during laparoscopic surgery compared to open surgery. Herein, we report a simple and easy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The prevention of BO is also an inevitable problem in laparoscopic surgery. Some studies have described a method of positioning Seprafilm in laparoscopic surgery to prevent BO and peritoneal adhesion [25][26][27] . However, reports concerning the usefulness of Seprafilm in laparoscopic surgery are few 28) .…”
Section: Introductionmentioning
confidence: 99%
“…The prevention of BO is also an inevitable problem in laparoscopic surgery. Some studies have described a method of positioning Seprafilm in laparoscopic surgery to prevent BO and peritoneal adhesion [25][26][27] . However, reports concerning the usefulness of Seprafilm in laparoscopic surgery are few 28) .…”
Section: Introductionmentioning
confidence: 99%
“…However, the fragile and sticky characteristics of Seprafilm cause many surgeons to hesitate from using it for deep surgical sites, such as the pelvic wall and retroperitoneal surface, with laparoscopic techniques. There have been several studies that introduced different methods for the placement of Seprafilm during laparoscopic surgery, such as grasping and rolling it directly with forceps, 3–5 wrapping it with its backing paper, 6,7 and using an introducer 8–11 . Although those methods are well‐designed and performed placement of Seprafilm with high success rates, some weak points remain.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this method needs no special equipment, except gauze. Some previous reports introduced other methods by using special equipment—introducers such as a reduction sleeve (KARL STORZ GMBH & CO, Tuttlingen, Germany 9,10 ) (Integra, Plainsboro, USA 11 ) or an adhesion prevention sheet introducer (Hakko, Tokyo, Japan 8 ), which are only used for the application of Seprafilm with extra costs. On the other hand, our method requires only gauze, which is generally used for multiple purposes during laparoscopic surgery and has an economical advantage.…”
Section: Discussionmentioning
confidence: 99%
“…However, with our method we were able to use the top three layers without moisture or stickiness. Additionally, Sumi et al reported that their method with the reducer sleeve could easily overcome the Seprafilm's susceptibility to tearing, which makes it unmanageable to spread out in the abdominal cavity (8). These previous techniques were simple and helpful for surgeons, but they are not widely used.…”
Section: Discussionmentioning
confidence: 99%